Research Note: How Valuable are Organizational Capabilities? - Collis, David J. (Strategic Management Journal, 1994)
Organizational capabilities, appropriately defined, can meet the conditions, articulated by the resource-based view of the firm, for being a source of sustainable competitive advantage. However, this paper observes that there are limits to the extent of the importance of such capabilities. They are vulnerable to threats of erosion, substitution, and above all to being superseded by a higher-order capability of the ‘learning to learn’ variety. This suggests that there can be an infinite regress in the explanation for, and prediction of, sustainable competitive advantage. The problem is resolved by arguing that the value of organizational capabilities is context dependent, and by recognizing that the strategy field will never find the ultimate source of sustainable competitive advantage.